Tourism and Tradition: How Community-Based and Ethnic Tourism Are Reshaping Chin Traditional Tattoos in Myanmar - Bawi, Salai (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
In response to the increasing interest in local cultures and the preservation of heritage, the tourism industry has evolved beyond traditional leisure and recreation activities. This evolution has led to a surge in initiatives aimed at safeguarding the cultural identity, heritage, and traditions of developing nations. In the context of chin state in Myanmar, the resurgence of tradtitional face tattoos, onece less prevelent, can be attributed to the rising tourism activity in the region. This study hightights how facial tattors have been commercialized within the tourism sector, influenced by religious and ethnic dynamics. The commodification of these facila tattoos has paradoxically contributed to the preservation of this cultural practice among the Chin tribes by imbuing it with symbolic significance in the realm of ethnic tourism. Moreover, the processes of ethnic tourism have played a crucial role in reviving indigenenous knnowledge and promoting cultural sustainability in Myanmar.By intertwining tourism initiatives with the preservation of cultural heritage, ethnic tourism has emerged as a vehicle for revitalizing traditional practices and forstering a deeper appreciation for the cultural identity of the chin tribes. This intertwining of tourism and cultural sustainability underscores the importance of ethnically engaging with local communties and traditions to ensure the authenticity and longevity of cultural heritage in the face of evolving tourism landscapes.